Encyclopedia of analytical chemistry: supplementary volumes S1-S3 : applications, theory and instrumentation - Meyers, Robert A. (Robert Allen), 1936- (Chichester, West Sussex : Wiley, 2011)
'The new 3-Volume Supplementary Set for Encyclopedia of Analytical Chemistry contains 95 new chapters (published online in Encyclopedia of Analytical Chemistry (EAC) from 2008 - 2010), covering subjects which have achieved particular prominence and distinction since the print publication of EAC in 2001. The new 3 Volume Set includes advances and theory ranging from mass spectrometry, atomic, infrared, Raman and X-ray spectroscopy, to nuclear magnetic resonance and imaging, nuclear methods, electrochemistry, and hyphenated techniques, as well as atomic force spectroscopy applications. Provides essential information required to analyze elements and compounds as well as structures in a wide variety of matrices for a range of applications, interpret the results and also gain a thorough knowledge of the theory and instrumentation utilized. Coverage of key advances includes: Proteomics and genomics Coverage of quantitative proteomics, electrochemical detection, dynamic light scattering, amyloids and protein aggregation measurements to low-cost, high-throughput gene sequencing Imaging technologies Coverage of major new medical and biological techniques including: ultrashort laser pulse medical imaging, quantitative imaging of membrane mechanics with molecular resolution, 3D neutron imaging, scanning near-field ultrasound holography, atomic force microscopy in nanocell biology, biomolecular interactions using nanopore force spectroscopy, scanning electrochemical microscopy and quadrupolar nuclei in biological systems Nanotechnology Expanded coverage of nanotechnology including scanning probe microscopy for imaging nanoparticles and nanocrystals, nanomaterials for electroanalysis, as well as scanning electrochemical microscopy, and scanning near-field ultrasound holography Other major advances There is also comprehensive coverage of advances in environmental monitoring, drinking water analysis, forensic science, electronic absorption and luminescence spectroscopy, infrared spectroscopy, atomic spectroscopy, nuclear magnetic resonance and electrochemistry; as well as specific coverage in pharmaceuticals and drugs, clinical chemistry, X-ray spectrometry, chemometrics, polymers and liquid chromatography Suitable for chemists (organic, polymer, inorganic, biochemist, molecular biologist as well as, of course, an analytical chemist), physicists or engineers (environmental, industrial or materials).' --
'This Work is proposed as three supplementary volumes publishing 10 years after the original publication of the Encyclopedia of Analytical Chemistry (EAC). EAC provides a much-needed professional level reference work and is the most comprehensive analytical chemistry reference available, covering all aspects from theory and instrumentation through to applications and techniques'--
Includes bibliographical references and index.
Keywords: Chemistry, Analytic -- Encyclopedias; SCIENCE / Chemistry / Analytic